Pengaruh Pemeliharaan Mesin Kerja Dan Pesediaan Bahan Baku Terhadap Proses Poduksi Dengan Kualitas Bahan Baku Sebagai Variabel Moderating (Studi Kasus : Home Industry Mebel Lia Pabot Kec. Percut Sei Tuan) - Wahidah, Nurul; Bi Rahmani, Nur Ahmadi; Yanti, Nursantri (Universitas Labuhanbatu, 2022)
The purpose of this study was to analyze the effect of maintenance of working machines, Raw Material Inventory with Quality of Raw Materials as a Moderating Variable in the home industry furniture lia furniture on production levels. Indonesia is one of the largest archipelagic countries in the world, Indonesia has more than ten thousand islands which have abundant natural resources. The potential of forest products in Indonesia can be said to have the opportunity to become the most important economic sector for the country. One sector that is directly related to the utilization of forest products is the industrial sector. The furniture industry is one of the prima donnas for certain areas, especially in Percut Sei Tuan District, recently the furniture industry has been in the spotlight in various regions, even though the furniture industry has experienced ups and downs due to competition with imported products. Based on the production factors which consist of several indicators, one of which is the maintenance of work machines and the supply of raw materials with the quality of raw materials, they have a quite influential role in the production process in any industry. The aim of this research is to find out, analyze to understand its effect on the production process.